THE ROLE OF KNOWLEDGE SHARING IN ACHIEVING JOB PROFICIENCY: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES IN THE SALAH AL-DIN DIRECTORATE OF EDUCATION - Aliaa Ibrahim Hussein; Bassam Ali Khalid; Dalal Salih Mahdi (Scholars Digest Publishing, 2025)
The current study was conceived with aim of establishing the role that knowledge sharing in achieving job proficiency among a sample of Salah Al-Din Educational Directorate staff. To achieve the objectives and test the study hypotheses, a conceptual framework was developed for the purpose of ascertaining the logical relationships between the variables under scrutiny and their dimensions. We utilized the descriptive analytical method to analyze the data related to the research problem and to reach conclusions. For data collection, we designed questionnaire as a key tool for this type of tasks. The Salah Al-Din Educational Directorate was selected as a research field, along with a sample of 130 employees. Of these, 110 were deemed valid and thus were retrieved for statistical analysis. Results emerging from the study yielded several outcomes that are in line with its hypotheses. The main finding involved job efficiency which was found to be positively and significantly influenced by the various aspects of the main variable (i.e. knowledge-sharing) in the organization. This relationship has been found to be strong across sub-dimensions as well. The researchers came up with a number of recommendations.
Keywords: Knowledge sharing, Job Proficiency, Salah Al-Din Education Directorate.